THE FRENCH STANCE TOWARDS THE POLISH PEOPLE’S REPUBLIC FROM THE ELECTION OF FRANÇOIS MITTERRAND TO THE LIFTING OF MARTIAL LAW AS ASSESSED BY POLISH DIPLOMATS - Mateusz Piotr GANCEWSKI (Humanities and Social Sciences)
This article aims to explain and assess how Polish diplomacy saw the French policy towards Poland from the beginning of the presidency of François Mitterrand to the suspension of martial law (1981–1982). It evaluates the reactions of the French state and the Socialist Party, the French Communist Party, and the French public opinion. The French state – adhering to the political principles of Charles de Gaulle – was faced with a real conundrum: what policy to pursue when it came to the Polish crisis? Conflicting interests made it act indecisively. Its policies and motives were all closely observed by the Polish diplomacy. This article further proves that Polish foreign policy, though not sovereign, was not ideologically driven (besides official declarations) as the assessment of the French foreign policy demonstrates.